2014
DOI: 10.1038/bjc.2014.192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathologically insignificant prostate cancer is not accurate in unscreened men

Abstract: Background:Identification of men harbouring insignificant prostate cancer (PC) is important in selecting patients for active surveillance. Tools have been developed in PSA-screened populations to identify such men based on clinical and biopsy parameters.Methods:Prospectively collected case series of 848 patients was treated with radical prostatectomy between July 2007 and October 2011 at an English tertiary care centre. Tumour volume was assessed by pathological examination. For each tool, receiver operator ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…A number of studies have shown that in around half of men undergoing radical prostatectomy, the prediction of grade and/or stage is wrong [2][3][4]. The true degree of diagnostic error is difficult to ascertain as those men with a negative TRUS biopsy do not usually undergo a more accurate verification test.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that in around half of men undergoing radical prostatectomy, the prediction of grade and/or stage is wrong [2][3][4]. The true degree of diagnostic error is difficult to ascertain as those men with a negative TRUS biopsy do not usually undergo a more accurate verification test.…”
Section: Introductionmentioning
confidence: 99%
“…A 50.2% upgrading was recently found when comparing TRUS biopsy to subsequent radical prostatectomy (RP) Gleason score (GS) [7] and cancers with initial negative TRUS have a 37% underdiagnosis [5,8] . Uncertainty that is inherent in the standard diagnostic pathway has resulted in increasing use of transperineal biopsies.…”
mentioning
confidence: 99%
“…3 Upgrading rates up to 50% were reported when RP specimens were used as the reference test. 4 Therefore, there is a need for new diagnostic tools that might improve the estimation of tumor grade and extent, and the selection of patients for AS.…”
mentioning
confidence: 99%